Horizontal Gene Transfers from Bacteria to Entamoeba Complex: A Strategy for Dating Events along Species Divergence - Miguel Romero; R. Cerritos; Cecilia Ximenez (Journal of Parasitology Research)
Horizontal gene transfer has proved to be relevant in eukaryotic evolution, as it has been found more often than expected and related to adaptation to certain niches. A relatively large list of laterally transferred genes has been proposed and evaluated for the parasite Entamoeba histolytica. The goals of this work were to elucidate the importance of lateral gene transfer along the evolutionary history of some members of the genus Entamoeba, through identifying donor groups and estimating the divergence time of some of these events. In order to estimate the divergence time of some of the horizontal gene transfer events, the dating of some Entamoeba species was necessary, following an indirect dating strategy based on the fossil record of plausible hosts. The divergence between E. histolytica and E. nuttallii probably occurred 5.93 million years ago (Mya); this lineage diverged from E. dispar 9.97 Mya, while the ancestor of the latter separated from E. invadens 68.18 Mya. We estimated times for 22 transferences; the most recent occurred 31.45 Mya and the oldest 253.59 Mya. Indeed, the acquisition of genes through lateral transfer may have triggered a period of adaptive radiation, thus playing a major role in the evolution of the Entamoeba genus.